Penerapan Metode K-Means Dalam Mengelompokkan Tingkat Kesembuhan Penderita Covid-19 - Sunardi, Hastha (Teknomatika, 2021)
The coronavirus pandemic (Covic-19) that began to be heard in Indonesia around the end of February 2020 seems to continue, where none of the experts from one discipline are able to predict this pandemic, when it ends. Unlike previous research that focused more on the extent of the spread of Covid-19. This research applies the K-Means method to focus on grouping the cure rate of patients exposed to Covid-19 with a self-isolation healing process. There is no difference in sex in the transmission process, so gender data is used as a id_penderita and not nominal type, so there is no need for initialization process. Therefore, it is quite interesting to analyze that the age, length of isolation, and number of family members is related to the spread of Covid-19 and is more focused on grouping healing rates with self-isolation. As for the average value for each cluster, the highest average value for age is found in cluster 3 at 53.8 years and the lowest in cluster 2 by 30 years. For the length of isolation the longest average value in cluster 1 is 29.7 days and the fastest in cluster 3 is 14 days.